Mandatory Participation in Occupational Pension Schemes in the Netherlands and other Countries - Damiaan H.J. Chen; Roel Beetsma (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper discusses mandatory participation in Dutch occupational pension schemes. While mandatory participation is a historical feature of most second-pillar pension arrangements, some recent developments may affect the case for mandatory participation. The main ones are the revision of the Dutch supplementary pension contract, changes in the prudential supervisory rules and developments in European regulations regarding supplementary pensions. We also compare mandatory participation in the Dutch occupational pension system with that in a number of foreign pension systems.
Keywords: H55; J26; 330